Attitudes of CAMP interns toward their professions and their patients - Abanilla, Maria Zenaida L. (2002)
Attitude is often an overlooked aspect of education and is usually a result of incidental learning. With the high standards that society demands of health professionals, we can no longer take the chance that our students will develop the attitudes that we require of them. For the faculty to have more relevant affective curriculum, it is necessary to find out what attitudes CAMP interns develop as of the current curriculum. The objectives of this study were to determine the attitudes of CAMP interns regarding their professions and their patients, to describe the perceived factors influencing them, and to determine differences of attitudes across the three groups of students. The method of gathering data was through the use of an especially designed attitude rating scale, moral dilemmas, and discussions with a group of interns and three clinical supervisors. The rating scale was previously designed and tested on a group of interns and was modified accordingly. This was administered to the PT, OT and SP interns within a span of four weeks. Out of 99 respondents, only 67 replied for a response rate of 68%. Of the 67 subjects, 43 were PTs, 17 were OTs, and 7 were SPs. The results of the survey were tallied and grouped according to attitudes and groups of students. Using descriptive statistics and analysis of variance, items with low scores and significant differences were singled out. The students achieved a score of at least four in 13 out of 16 constructs. These are concern for patients, lack of cynicism, communication skills, volunteerism, respect for patient, responsibility and accountability, ethics, professional relationships, sensitivity, role in society, honor and integrity, presence of role models, and research. These were supported by the results of the moral dilemmas. There were significant differences in the constructs of concern for patients, lack of cynicism and research. The PTs scored the highest in the three constructs while the OTs scored the lowest for concern for patients and research and the SPs scored the lowest for lack of cynicism. Most of the students prefer to manage pediatric patients while agreeing that they do not make better patients. It is the motivation and disposition of the patient that makes them better patients. Overall, CAMP interns have a positive view of their patients and their professions. The existence of significant differences across the three groups of students leads to the acceptance of the alternative hypothesis; that there exists a significant difference across groups of students that was more apparent in three constructs. However, this difference does not translate into a more positive or more negative attitude towards their professions and patients. The researcher recommends the following to further improve this study. First ensure a more efficient system of administering the data collection tool with the researcher physically present when the subjects accomplish the tool. Second, perform a thorough statistical analysis prior to the conduct of the focus group discussion to ensure that all important points are covered in the discussion. This includes constructs and individual items with very high and very low scores, and those presenting with a significant statistical difference. Third, expand the selection for the clinical supervisors to include those from other affiliation centers. And lastly, document the discussions on video.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Attitudes